Management of BOS Funds Using the School Activity and Budget Plan Application (ARKAS) at Public Junior High Schools in Majalengka Regency - Joko Setiyono; Munir Munir; Dedy Achmad Kurniady; Taufani C. Kurniatun (Universitas Negeri Malang, 2025)
Abstract: This study aims to describe the financial management of the School Operational Assistance (BOS) funds using the School Activity and Budget Plan Application (ARKAS) at the junior secondary school level. A descriptive qualitative method was employed, with data collected through in-depth interviews, direct observations, and document analysis conducted in two public schools located in Majalengka Regency, West Java. The findings reveal that ARKAS significantly enhances the effectiveness, efficiency, and accountability of BOS fund management. It facilitates need-based activity planning, systematic financial documentation, and integrated reporting aligned with official regulations and monitoring mechanisms. Features such as automatic validation and user activity logs reinforce accountability, while the locking system reduces opportunities for budget manipulation. However, the study also identifies several challenges, including limited human resource readiness, insufficient ICT infrastructure in some areas, and the lack of active involvement of school committees in financial planning and evaluation processes. These limitations suggest that successful implementation of ARKAS requires not only technological tools but also continuous capacity building, improved digital literacy, and sustained technical assistance from education authorities. Therefore, ARKAS must be seen as a strategic reform instrument for strengthening school financial governance, rather than merely a technical solution. Keywords: School Operational Assistance (BOS), School Activity and Budget Plan Application (ARKAS), school financial management, transparency, digitalization